Panoramic radiographic features that predict the development of bisphosphonate-related osteonecrosis of the jaw - Kubo, Ryota; Ariji, Yoshiko; Taniguchi, Tohru; Nozawa, Michihito; Katsumata, Akitoshi; Ariji, Eiichiro (Oral radiology, 2018)
Objectives The purpose of this study was to clarify which panoramic radiographic features can predict the development of bisphosphonate-related osteonecrosis of the jaw (BRONJ). Methods Participants included 24 patients treated with bisphosphonates (BP) for osteoporosis who developed osteonecrosis of the jaw (ONJ + group). Controls included 179 patients treated with BP who did not have osteonecrosis (ONJ − group) and 200 patients with no history of BP administration (unmedicated group). The mandibular cortical width, mandibular cortical index (MCI), sclerosis of trabecular bone, and thickening of the lamina dura were evaluated on panoramic radiographs. Results The mandibular cortical width was significantly smaller in the ONJ – group than in the other groups. Class II MCI (semilunar defects of endosteal margin) was frequently noted on the affected and contralateral sides in the ONJ + group but not in the ONJ − or unmedicated groups. Sclerosis of the trabecular bone was significantly more frequently observed on the affected side in the ONJ + group than in the other groups. Thickening of the lamina dura was observed significantly more frequently in the BP-treated groups than in the unmedicated group. Conclusions Class II MCI may be an indicator to predict the development of BRONJ. Sclerosis of trabecular bone was a characteristic imaging feature of BRONJ. Thickening of the lamina dura may be an imaging feature caused by BP administration.